Seizure Incidence Rates in Children and Adults With Familial Cerebral Cavernous Malformations. (21st September 2021) - Fox, Christine K.; Nelson, Jeffrey; McCulloch, Charles E.; Weinsheimer, Shantel; Pawlikowska, Ludmila; Hart, Blaine; Mabray, Marc C.; Zafar, Atif; Morrison, Leslie; Zabramski, Joseph M.; Akers, Amy; Kim, Helen
Abstract : Background and Objectives: Seizure incidence rates related to familial cerebral cavernous malformation (FCCM) are not well described, especially for children. To measure the seizure incidence rate, examine seizure predictors, and characterize epilepsy severity, we studied a cohort of children and adults with FCCM enrolled in the Brain Vascular Malformation Consortium (BVMC). Methods: Seizure data were collected from participants with FCCM in the BVMC at enrollment and during follow-up. We estimated seizure probability by age and tested whether cerebral cavernous malformation (CCM) counts or genotype were associated with earlier seizure onset. Results: The study cohort included 479 FCCM cases. Median age at enrollment was 42.5 years (interquartile range 22.5–55.0) and 19% were children (<18 years old). Median large CCM count was 3 (interquartile range 1–5). Among 393 with genotyping, mutations were as follows: CCM1 (Common Hispanic Mutation) (88%), another CCM1 mutation (5%), CCM2 mutations (5%), and CCM3 mutations (2%). Prior to or during the study, 202 (42%) had a seizure. The cumulative incidence of a childhood seizure was 20.3% (95% confidence interval [CI] 17.0–23.4) and by age 80 years was 60.4% (95% CI 54.2–65.7). More total CCMs (hazard ratio [HR] 1.24 per SD unit increase, 95% CI 1.1–1.4) or more large CCMs (HR 1.5 per SD unit increase, 95% CI 1.2–1.9) than expected for age and sex increased seizure risk. A CCM3 mutation also increased risk compared to other mutations (HR 3.11, 95% CI 1.15–8.45). Individuals with a seizure prior to enrollment had increased hospitalization rates during follow-up (incidence rate ratio 10.9, 95% CI 2.41–49.32) compared to patients without a seizure history. Discussion: Individuals with FCCM have a high seizure incidence and those with more CCMs or CCM3 genotype are at greater risk. Seizures increase health care utilization in FCCM.